Numerical simulation of cavitating flow around a twist hydrofoil focusing on the erosion behaviour. Issue 1 (1st April 2022) - Wang, Zhengdong; Li, Linmin; Li, Xiaojun; Zhu, Zuchao
Abstract: The erosion risk in cavitating flow is a challenging issue due to the instantaneity and complexity. In this paper, the energy balance approach (EBA)-based cavitation erosion model is employed to investigate the erosion behavior around a Delft Twist-11 hydrofoil utilizing large eddy simulation (LES) approach. The results show that the predicted erosion region is qualitative agreement with the experimental paint tests. The adaptive mesh refinement (AMR) method is conducted on a coarse mesh to verify its preponderance in save computing resources and ensuring accuracy. It is found that the case using AMR obtains more accurate cavitation features within less computational cells than that of the fine mesh, including the predicted shedding frequency and U-type structure of shedding cloud.